An overview on desiccation-tolerant mat-forming monocotyledons on tropical inselbergs - Porembski, Stefan; Rexroth, Juliane; Weising, Kurt; Bondi, Luiz; Mello-Silva, Renato; Centeno, Danilo C.; Datar, Mandar N.; Watve, Aparna; Thiombano, Adjima; Tindano, Elycée; Rabarimanarivo, Marina N.; de Paula, Luiza F.A. (Flora. Morphologie, Geobotanik, Oekophysiologie, 2021)
•Tropical inselbergs are centers of diversity for desiccation-tolerant mat-forming monocots.•Cyperaceae, Poaceae and Velloziaceae are the main Poikilohydric monocot families on tropical inselbergs.•Species diversity and endemism of Poikilohydric monocot-mats varies considerably along the tropics. Desiccation-tolerant mat-forming monocotyledons (DTMFM) are typical constituents of the vegetation of tropical inselbergs. The latter are old granitic / gneissic rock outcrops that rise abruptly above the surrounding landscape. Due to unpredictable droughts, they are centers of diversity for dry adapted species such as vascular resurrection plants (poikilohydric species). Carpet-like mats formed by highly specialized DTMFM occur on open, partly steep slopes where they are firmly glued to the underlying rock. These mats are widespread on both Neotropical (mainly Brazil) and Paleotropical (Africa, Madagascar, India) inselbergs. Within angiosperms, exclusively members of Cyperaceae, Poaceae and Velloziaceae are DTMFM. Here, we compiled 32 DTMFM species on tropical inselbergs. Nevertheless, since ecophysiological studies focused on this particular group of plants are still incipient, we expect that many more species display this strategy on tropical inselbergs. Our overview provides updated insights into selected biogeographical, ecological and molecular aspects of DTMFM.